Perancangan dan Implementasi Aplikasi Penjualan CnG Indonesian Product Berbasis Android dengan Metode White Box - Candra Galang Gemilang Putra; Abdul Aziz (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
At this time, mobile-based applications, especially Android, have been widely used by the community, along with the increasingly easy devices used and commonly referred to as smartphones. In this regard, of course, many applications are developed on a mobile basis and can be used by anyone via a smartphone. CnG Indonesian Products are MSMEs (micro, small, and medium enterprises) that are engaged in the fashion sector, ranging from daily clothing to convection needs for an event. CnG Indonesian Product is still promoting through social media only, so the reach of the promotion still has limitations and has not been able to reach the entire community. In this study, an extension was carried out to build an Android-based application and its testing using the white box research method. The white box method will be implemented in an Android-based sales application and applied to CnG Indonesian Products. Data collection from this research was done by direct observation, literature study, field study and direct interview. The data used in this study uses the Java programming language which is supported by the Android studio supporting application with version 1.51. The results of testing sales applications using white boxes can find out about the internal workings of the software used.